2008
DOI: 10.1007/s00381-008-0659-8
|View full text |Cite
|
Sign up to set email alerts
|

Dislocation of a fractured mandibular condyle into the middle cranial fossa: a case treated by an extracranial approach

Abstract: The case is reported to emphasize the need for careful radiological investigation in case of condylar fractures and the effectiveness of the extracranial route to surgically treat these rare complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 11 publications
0
3
0
1
Order By: Relevance
“…Dislocation of the mandibular condyle to the mid-cranial fossa is a rare event, with 66 cases, the present case included, reported in the literature 4514151617181920212223. Rosa et al reported 55 cases using Medline and PubMed search engines between 1960 and 2005.…”
Section: Discussionmentioning
confidence: 90%
“…Dislocation of the mandibular condyle to the mid-cranial fossa is a rare event, with 66 cases, the present case included, reported in the literature 4514151617181920212223. Rosa et al reported 55 cases using Medline and PubMed search engines between 1960 and 2005.…”
Section: Discussionmentioning
confidence: 90%
“…In cases with a late diagnosis, the dislocated condyle and fragments of the fossa can be adhered, and forceful reduction can result in an intracranial injury. Therefore, a condylectomy [9,10,17,26,68,89], condylotomy [4,7,44,49,52,63,69], or gap arthroplasty [5,33,60,95] is required.…”
Section: Etiology and Treatment Of Intracranial Dislocation Of The Co...mentioning
confidence: 99%
“…After open reduction, the glenoid fossa should be reconstructed to ensure separation from the cranial cavity and re-establish a functional articulation using autogenous or alloplastic material, including bone [17,35,38,42,45,49,51,[55][56][57][58][59]66,68,80,84,97,98,102], cartilage [52,58,60,69], temporalis fascia [29,37,64,71,80,95,101,109], temporalis muscle [62,63,73,96,103,106], titanium plates [40,47,81,88,89], silicon [22,37], Silastic [16], Gelfoam [7], or Duragen [86] (Table S2). Reconstruction of the condyle is required t...…”
Section: Etiology and Treatment Of Intracranial Dislocation Of The Co...mentioning
confidence: 99%
“…Існують три основні процедури для лікування ТДГНЩ до черепної порожнини [4,[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]: 1) закрите переміщення головки нижньої щелепи під загальною анес тезією, 2) відкрита хірургічна корекція з краніотомією, 3) кондилотомія. Оптимальний спосіб лікування обирають індивідуально залежно від КТкартини [4,9,21].…”
Section: ключові слова: головка нижньої щелепи; середня черепна ямка;unclassified